The Contributions of Fiber Atrophy, Fiber Loss, In Situ Specific Force, and Voluntary Activation to Weakness in Sarcopenia. (26th February 2018) - McPhee, Jamie S; Cameron, James; Maden-Wilkinson, Thomas; Piasecki, Mathew; Yap, Moi Hoon; Jones, David A; Degens, Hans
Abstract: The contributions of fiber atrophy, fiber loss, in situ specific force, and voluntary activation to weakness in sarcopenia remain unclear. To investigate, 40 older (20 women; age 72 ± 4 years) and 31 younger adults (15 women, age 22 ± 3 years) completed measurements. The knee extensor maximal voluntary torque (MVC) was measured as well as voluntary activation, patella tendon moment arm length, muscle volume, and fascicle architecture to estimate in situ specific force. Fiber cross-sectional area (FCSA), fiber numbers, and connective tissue contents were also estimated from vastus lateralis biopsies. The MVC, quadriceps volume, and specific force were 39%, 28%, and 17% lower, respectively, in old compared with young, but voluntary activation was not different. The difference in muscle size was due in almost equal proportions to lower type II FCSA and fewer fibers. Five years later ( n = 23) the MVC, muscle volume and voluntary activation in old decreased an additional 12%, 6%, and 4%, respectively, but there was no further change in specific force. In situ specific force declines relatively early in older age and reduced voluntary activation occurs later, but the overall weakness in sarcopenia is mainly related to loss of both type I and II fibers and type II fiber atrophy.